Integrasi Teknologi dalam Pendidikan Karakter: Membangun Generasi Berkarakter di Era Digital - I'tikaf, M. Arwan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is Technology Integration in Character Education: Building a Generation with Character in the Digital Era. The type of research is a literature review. Research results: The integration of technology in character education is a strategic step to build a generation of character in the digital era. Technology is not only a learning tool, but also a medium for instilling moral, ethical and cultural values ​​that are relevant to the challenges of the times. By utilizing interactive digital platforms, gamification, and value-based educational content, educators can create engaging and meaningful learning experiences. However, the success of this integration requires collaboration between educators, parents and the community to ensure that technology is used wisely, purposefully and in accordance with the goals of character education. With this holistic approach, it is hoped that future generations will be able to face the complexity of the digital world without losing their identity and noble values